Left-Behind Children and Return Decisions of Rural Migrants in China - Sylvie Démurger; Hui Xu (Institute for the Study of Labor (IZA), 2013)
This paper examines how left-behind children influence return migration in China. We first present a simple illustrative model based on Dustmann (2003) that incorporates economic and non-economic motives for migration duration (or intentions to return), among which are parents' concerns about the well-being of their left-behind children. We then propose two complementary empirical tests based on data we collected from rural households in Wuwei county (Anhui province) in fall 2008. We first use a discrete-time proportional hazard model to estimate the determinants of migration duration for both on-going migrants with an incomplete length of duration and return migrants with a complete length of duration. Second, we apply a binary Probit model to study the return intentions of on-going migrants. Both models yield consistent results regarding the role of left-behind children as a significant motive for return. First, left-behind children are found to draw their parents back to the village, the effect being stronger for pre-school children. Second, sons are found to play a more important role than daughters in reducing migration duration.
Keywords: J61; J13; C41; C25; O53; 330; left-behind children; migration duration; return migration; discrete-time duration analysis; China